ISLAM, FEMINISME, DAN GENDER - Ahmad Musyaddad Nur Basyir Basyir; Muhammad Zia Ul-Haq Hilman; Rizka Muharamah (Melati Institute, 2023)
This research aims to discuss Islam, feminism and gender. This research uses a qualitative approach by applying the descriptive-analytical method. The results of this study show that Islam comes with a moral message of humanity that is unmatched by other religions. Islam came to liberate humans from the shackles of humanity filled with ignorance and injustice. Islam came with a mission of equality between human beings. Because, the glory on Allah's side is the value of piety. Thus, it is expressly said, no single power can suppress and discriminate for individual freedom with other individuals. Respect for women occurred during the life of the Islamic community during the prophetic period of Muhammad s.a.w, where in carrying out activities, both worldly and ukhrowi, Rasullullah never differentiated between men and women. Because each individual has the same rights and obligations Translated with www.DeepL.com/Translator (free version)